Counteracting the Impact of Online Gender-Based Violence of False Allegations Using the 5R Method on UNIMUDA Sorong Students, Southwest Papua - Muhamad Hasan Rumlus; Agfajrina Cindra Pamungkas; Nadila (Yayasan Ilomata, 2026)
Advances in digital technology in addition to bringing benefits also pose new risks in the form of Online Gender-Based Violence (KBGO), one of which is false accusations or false accusations that can damage students' reputations. This condition is rampant in the campus environment, including at UNIMUDA Sorong, Southwest Papua, where students are a vulnerable group due to low digital literacy in identifying and handling KBGO cases. The research method used was a quantitative approach through a survey of 159 students with two stages, namely a pre-test to measure initial understanding and a post-test to see the impact of the intervention. The results showed a significant improvement in students' understanding of KBGO, courage to refuse, and case reporting skills after the intervention. The findings also point to other forms of GBV such as cyberbullying, impersonation, and non-consensual image sharing.